1982
DOI: 10.1530/jrf.0.0660491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medroxyprogesterone acetate on gestation in mink

Abstract: Mink ovariectomized 14 days after the first of two matings received injections of 2 mg MPA, the same MPA treatment + an oestradiol-17 beta implant or no replacement therapy. Some mink were ovariectomized after implantation and given a single dose of 2 mg MPA or no replacement therapy. MPA persisted in the serum at detectable levels for 13 or more days in all mink treated. MPA and MPA + oestradiol induced uterine growth but neither treatment was capable of inducing embryo implantation. More embryos were retaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Murphy et al (1982,1983) showed the importance of ovarian factors in implantation by demonstrating that ovariectomy during embryonic quiescence consistently prevents implantation. Exogenous progesterone or medroxyprogesterone acetate failed to correct the situation and pregnancies could not be shortened by this treatment (Hansson, 1947;Hammon, 1951b;Holcomb, 1967;Murphy et al, 1982Murphy et al, , 1983Murphy, 1983a;Christiansen, 1985). Contrary to these findings, some investigators (Concannon et al, 1980;Jarosz & Dukelow, 1985) found evidence that medroxyprogesterone could advance the time of implantation.…”
Section: Oogénesis and Ovulationmentioning
confidence: 96%
“…Murphy et al (1982,1983) showed the importance of ovarian factors in implantation by demonstrating that ovariectomy during embryonic quiescence consistently prevents implantation. Exogenous progesterone or medroxyprogesterone acetate failed to correct the situation and pregnancies could not be shortened by this treatment (Hansson, 1947;Hammon, 1951b;Holcomb, 1967;Murphy et al, 1982Murphy et al, , 1983Murphy, 1983a;Christiansen, 1985). Contrary to these findings, some investigators (Concannon et al, 1980;Jarosz & Dukelow, 1985) found evidence that medroxyprogesterone could advance the time of implantation.…”
Section: Oogénesis and Ovulationmentioning
confidence: 96%
“…Further, a single estrogen injection terminates diapause in rodents (Dey et al 2004). Treatment of carnivores in obligate (Murphy et al 1982) or marsupials in seasonal (Fletcher et al 1988) delay with estrogen does not induce reactivation of the embryo. Nonetheless, estrogens have pleiotropic mitogenic and mitotic effects on target tissues, mediated through classic nuclear receptors, membrane estrogen receptors and actions of multiple intracellular effectors (Frasor et al 2003) and may, in the appropriate concentration and temporal sequence, reactivate embryos in diapause.…”
Section: Regulation Of the Cell Cycle In Diapause And Reactivationmentioning
confidence: 99%
“…Removal of the ovaries and replacement with P4 during early pregnancy in the ferret maintained viable blastocysts in the uterus. An injection of estradiol, as in the mouse and rat on the same hormone regimen, did not cause implantation (65)(66)(67)). An unidentified 60-kDa protein had been shown to be necessary for embryo implantation in ferrets (68).…”
Section: Ferret-signal For Implantationmentioning
confidence: 88%